The English Convents in Exile, 1600ï¿1800 Communities, Culture and Identity - Kelly, James E.; Bowden, Caroline (London Taylor & Francis Ltd, 2024)
In 1598, the first English convent was established in Brussels and was to be followed by a further 21 enclosed convents across Flanders and France with more than 4,000 women entering them over a 200 year period. In theory they were cut off from the outside world; however, in practice the nuns were not isolated and their contacts and networks spread
Introduction Part I Communities 1 From Community to Convent: The Collective Spiritual Life of Post-Reformation Englishwomen in Dorothy Arundells Biography of John Cornelius 2 Essex Girls Abroad: Family Patronage and the Politicization of Convent Recruitment in the Seventeenth Century 3 Missing Members: Selection and Governance in the English Convents in Exile Part II Culture: Authorship and Authority 4 The Literary Lives of Nuns: Crafting Identities Through Exile 5 Naming Names: Chroniclers, Scribes and Editors of St Monicas Convent, Louvain, 1631-1906 6 Translating Lady Mary Percy: Authorship and Authority among the Brussels Benedictines 7 Barbara Constables Advice for Confessors and the Tradition of Medieval Holy Women 8 Shakespeares Sisters: Anon and the Authors in Early Modern Convents Part III Culture: Patronage and Visual Culture 9 Petitioning for Patronage: An Illuminated Tale of Exile from Syon Abbey, Lisbon 10 Parlour, Court and Cloister: Musical Culture in English Convents during the Seventeenth Century 11 Cloistered Images: Representations of English Nuns, 1600-1800 Part IV Identity 12 Archipelagic Identities in Europe: Irish Nuns in English Convents 13 Divine Love and the Negotiation of Emotions in Early Modern English Convents 14 Avoiding Rash and Imprudent Measures: English Nuns in Revolutionary Paris, 1789-1801
Keywords: 17. Jahrhundert (ca. 1600 bis ca. 1699); c 1600 to c 1700; Early modern history: c 1450/1500 to c 1700; General & world history; Geschichte allgemein und Weltgeschichte; HISTORY / World